Predictive Value of Blood Ammonia in the Prognosis of Acute Liver Failure Evaluated by Receiver Operating Characteristic Curves - Li, Lei; Liu, Peng; Li, Ke; Lin, Fang; Ji, Cheng-Cheng; Wang, Yong-Gang; Xu, Biao; Mu, Jin-Song; Zhou, Yue-Su (Turkish Journal of Gastroenterology, 2021)
Background/Aims: To investigate the predictive value of blood ammonia (BLA) quantification in the prognosis of acute liver failure (ALF). Materials and Method: Seventy-one patients with ALF were enrolled and the BLA concentration was measured in all patients. After following up for 28 days, patients were divided into two groups: the surviving group (n = 21) and the deceased group (n = 50). An independent-samples t-test was used to compare BLA concentrations between the two groups, and receiver operating characteristic curves were used to evaluate the predictive value of BLA in the prognosis of ALF. A four-fold table analysis was performed with the determined BLA cutoff value. Results: The average concentration of BLA in the deceased group was significantly higher compared with the surviving group (144.50 µmol/L vs. 106 µmol/L, respectively; P = 0.035). The cutoff BLA concentration for a good ALF prognosis was 122.5 µmol/L. The area under the curve was 0.659. Both the sensitivity and specificity were >0.6. The 95% confidence intervals for sensitivity and specificity were 0.452–0.733 and 0.477–0.878, respectively. The four-fold table analysis revealed a positive predictive value of 83.3%, a negative predictive value of 42.9%, a misdiagnosis rate of 28.6%, and an accuracy of 63.4%. Conclusion: With a cutoff BLA concentration of 122.5 µmol/L, the prognosis of ALF could be predicted with high sensitivity and specificity, a positive predictive value, a low misdiagnosis rate, and good accuracy.